Peran Brand Reputation dan Hedonic Motive terhadap Buying Decision serta Implikasinya pada Customer Satisfaction Produk Motor Suzuki di Kota Serang - Hidayat, Selamet; Sutisna, Sutisna; Umalihayati, Umalihayati (Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of brand reputation and hedonic motive on customer satisfaction through the buying decision variable. Using quantitative research methods. Respondents totaled 230 Suzuki brand motorbike users in Serang City. Data analysis tools use Smart PLS and SPSS. The research results show that partially there is a significant influence between the brand reputation and buying decision variables on customer satisfaction, but there is no significant influence between the hedonic motive variable on customer satisfaction. Simultaneously and partially, there is a significant influence between the brand reputation and hedonic motive variables on buying decisions. Indirectly, there is a significant influence between buying decisions through brand reputation and hedonic motives on customer satisfaction with Suzuki Motorbike products in Serang City.